Spatial Analysis for TB management in Chiang Rai Province - คชสาร, ทศพล (CRRU Law, Political Science and Social Science Journal, 2021)
This research about Spatial Analysis for TB management is aimed to study about 3 objectives are 1) to analyze the prevalence and density of tuberculosis patients in Chiang Rai Province, 2) to analyze tuberculosis epidemic risk areas in Chiang Rai Province, and 3) to propose a spatial management guideline for tuberculosis patients in Chiang Rai Province. This study was based on the prevalence and density of TB patients in Chiang Rai Province. Using geographic information system to apply with the information from the Public Health Office, Chiang Rai. There were 1,112 TB patients in the year 2019, analysis of the prevalence and density of tuberculosis patients classified by sub-district. The results showed that the areas with the highest number of TB cases were Doi Hang and Rob Wiang sub-districts. The area with the highest prevalence rate in Doi Hang Subdistrict, followed by Doi Lan Subdistrict and Huai Sak Subdistrict, respectively. The areas with the highest density of tuberculosis patients were Wiang Subdistrict, Mueang Chiang Rai District, followed by Rob Wiang Subdistrict and Doi Hang Subdistrict, respectively. When the prevalence and density of TB patients were analyzed together, three risk areas are Doi Hang sub-district, Wiang sub-district and Rong Wiang sub-district, respectively. The guideline of Spatial management for tuberculosis patients includes target area selection for personnel allocation / budget / Time period, inform a regulation, proactive services and health behaviors and creating or developing tuberculosis treatment networks.